Sudden cardiac arrest of a 16-year-old boy with left main coronary artery atresia: a case report. Issue 4 (9th June 2020) - Tomura, Nobunari; Nakagami, Takuo; Yamaguchi, Shinichiro; Yaku, Hitoshi; Patel, Peysh A
Abstract: Background: In many cases, the cause of exercise-induced cardiopulmonary arrest in young persons is thought to be fatal arrhythmia, and one of the causes is ischaemic heart disease. Left main coronary artery atresia (LMCAA) is an extremely rare disease in which there is a congenital defect of the left main coronary artery, causing heart failure and exercise-induced angina attacks at a young age. Thus, it is disease that should be differentiated when examining young persons with chest pain. Case summary: A 16-year-old boy experienced sudden cardiopulmonary arrest during soccer practice, was brought to our hospital for emergency treatment after return of spontaneous circulation. Elective coronary angiography revealed findings indicating an osmium defect in the left coronary artery (LCA) and blood flow via collateral circulation from the right coronary artery. Contrast-enhanced coronary computed tomography (CT) angiography showed a defect in the LCA ostium and LMCAA was diagnosed in the patient. After coronary artery bypass grafting was performed, but the patient was discharged in an ambulatory state with a wearable cardiac defibrillator. Postoperative course has been favourable. Discussion: Left main coronary artery atresia is an extremely rare disease in which there is a congenital defect of the left main trunk of the coronary artery and should be differentiated when encountering cases of heart failure or exercise-induced angina/arrhythmia attacks in young persons who are not at risk for atherosclerosis. Exercise electrocardiogram may show a false negative result, and therefore coronary CT is useful for diagnosis.